Studi Pustaka: Deskripsi Penerimaan Keluarga terhadap Pengungkapan Anak Autisme: Penerumaan Keluarga, Peran Keluarga, dan Keluarga Dengan Anak Autisme - Satya Aras Ardiansyah; Hastin Trustisari (Yayasan Literasi Sains Indonesia, 2024)
According to Loftus (2024), in the United States, 1 out of 36 children were diagnosed with autism in 2023, which is an increase compared to 2020 when it was 1 out of 44 children. Disclosure by healthcare professionals elicits various emotions within families such as disbelief, blaming God or oneself, ultimately leading to denial and neglect of children with autism. However, the family's role is crucial in the development of children, especially those with special needs like autism. The author here writes about the various emotional reactions of family members and the roles they undertake after the disclosure of a child's autism diagnosis, aiming to uncover the extent of family emotions and their role in the growth of children with autism. This research is conducted using a descriptive literature review method by describing and critiquing previously published journals. The results of this study indicate that the emotional reactions of family members are mostly negative, but positive emotional regulation can lead to better acceptance of the child. Stigmatization is one factor that contributes to negative emotions, but after receiving social support, families seek information about autism, followed by subsequent roles that help children with autism become independent and adaptive..